2014
DOI: 10.4103/0974-9233.142273
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Childhood Blindness and Functional Low Vision in the Eastern Mediterranean Region in 2012

Abstract: Childhood blindness and visual impairment (CBVI) are major disabilities that compromise the normal development of children. Health resources and practices to prevent CBVI are suboptimal in most countries in the Eastern Mediterranean Region (EMR). We reviewed the magnitude and the etiologies of childhood visual disabilities based on the estimates using socioeconomic proxy indicators such as gross domestic product (GDP) per capita and <5-year mortality rates. The result of these findings will facilitate novel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
1
24
0
3
Order By: Relevance
“…Childhood blindness and visual impairment are major disabilities that compromise normal childhood development and usually confer lifelong negative consequences on children. 5,8,9 The mean age of children included in this survey (9.3 + 3.5 years) was similar to a study carried out by Mehari in a rural central hospital in Ethiopia, where the children's ages ranged from 3 months to 15 years, with a mean age of 9.37 + 4.95 years. 10…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Childhood blindness and visual impairment are major disabilities that compromise normal childhood development and usually confer lifelong negative consequences on children. 5,8,9 The mean age of children included in this survey (9.3 + 3.5 years) was similar to a study carried out by Mehari in a rural central hospital in Ethiopia, where the children's ages ranged from 3 months to 15 years, with a mean age of 9.37 + 4.95 years. 10…”
Section: Discussionsupporting
confidence: 77%
“…Khandekar et al, in their review, found that the aetiology patterns of childhood blindness and visual acuity were divided according to 3 groups of high-, middle-, and low-income nations. 8 Cataract was the main cause of severe visual impairment in our study and is now replacing vitamin A deficiency and measles keratopathy as the main cause of blindness among children in Africa in some populations. 17 However, constraints of inadequate manpower and equipment for management in many parts of Africa 18 including Nigeria, still exists.…”
Section: Severe Visual Impairmentmentioning
confidence: 63%
“…Preporuke u skladu s motom SZO-a "Vision 2020 -Right to the Sight" Khandekar i suradnici daju preporuke za istočno mediteransku regiju u smislu probira na oštećenje vida na razini primarne zdravstvene zaštite. Autori naglašavaju važnost probira na oštećenje vida pri svakom posjetu liječniku radi cijepljenja, organizacije probira vida u predškolskoj dobi i upućivanja na oftalmološku obradu ako dijete nije prošlo testove probira 19 . I Gilbert i Khandekar ističu važnost obrazovanja subspecijalista dječjeg oftalmologa 2,19 .…”
Section: Stručnjaci Uključeni U Probir Na Oštećenje Vidaunclassified
“…Autori naglašavaju važnost probira na oštećenje vida pri svakom posjetu liječniku radi cijepljenja, organizacije probira vida u predškolskoj dobi i upućivanja na oftalmološku obradu ako dijete nije prošlo testove probira 19 . I Gilbert i Khandekar ističu važnost obrazovanja subspecijalista dječjeg oftalmologa 2,19 .…”
Section: Stručnjaci Uključeni U Probir Na Oštećenje Vidaunclassified
“…Childhood blindness alone accounted for 28.7% of the economic burden of blindness in India . The prevalence of childhood blindness in low‐income countries comprising Asia is estimated to be 0.9/1000 children …”
Section: Introductionmentioning
confidence: 99%